(untitled) (UNED Research Journal, 2020)
Introduction: Marital environment can contribute to similarities in lifestyle and morbidity between spouses, as they share common life habits and health risks. Objective: To investigate concordance between various risk factors for cardiovascular disease in couples of Costa Rican spouses. Methods: We analyzed 1084 couples from the Costa Rican Longevity and Healthy Aging Study. We used Pearson´s correlation coefficients, and Multivariate within-pair correlations obtained by analyzing dyadic data in the context of the Actor-Partner Interdependence Model (APIM). To estimate the APIM we used structural equation models, and logistic regression analyses to calculate the odds ratio of a spouse’s presenting one risk factor on the basis of the other spouse’s risk factor status. Results: After adjustment for age, smoking and physical activity, the strongest spousal concordance was for body mass index (r = 0,108, 95% confidence interval: 0,04 - 0,14) and the lowest for C reactive protein (r = 0,067: 0,01 - 0,16). People whose spouse has diabetes, hypertension, central adiposity, high body mass index or inflammation are more likely to have the same disease. The adjusted odds ratios were 2,837 (95% confidence interval: 2,02 – 3,98) for diabetes; 1,357 (1,06 – 1,74) for hypertension; 1,508 (1,08 – 2,10) for central adiposity; 1,777 (1,25 – 2,53) for high body mass index; and 1,357 (1,02 – 1,80) for inflammation. Conclusions: There is a small, but significant, spousal concordance between the different risk factors for cardiovascular disease.